The addiction to power and loneliness of the powerful. Deciphering ideological and psychosocial aspects that hinder human coexistence in Peru - Montero López, Víctor (2019)
The addiction to power and loneliness of the powerful are two phenomena that influence national life, generating repercussions that affect social relations. It was used as instruments surveys, participant observations, analysis of historical evidence such as ceramics, paintings, metallurgy, architectural remains, documents, etc., media content analysis, semiotic analysis, and documentary research and bibliographic The aim is to deepen the psychosocial aspects that explain them, to contribute to overcoming these phenomena that limit individual and social growth in Peru.